The Influence of Inflation, Deposit Interest Rate, and GDP on the Yield of Indonesia’s Fr0091 Government Bond in the 2021-2025 Period - Nasuha, Firly Kania; Maski, Ghozali (Contemporary Studies in Economic, Finance and Banking, 2026)
Government bonds are a vital instrument for financing the state budget deficit. This study examines the influence of inflation, deposit interest rates, and Gross Domestic Product (GDP) on the Yield to Maturity (YTM) of Indonesia government bond series FR0091 over the period 2021-2025. The method employed is Principal Component Regression (PCR) using quarterly data. The results indicate that inflation has a positive relationship with bond yield through the Fisher Effect mechanism. Deposit interest rates show a negative relationship with yield, suggesting that increased banking liquidity drives higher demand for bonds. Meanwhile, GDP exhibits a positive relationship with yield, reflecting increased de-mand for funds in financial markets during economic growth. These findings provide im-plications for monetary and fiscal policy, as well as government bond investment strate-gies.